Kajian Yuridis Terhadap Peraturan Menterial Pendidikan Nasional No 28 Tahun 2010 Tentang Penugasan Guru Menjadi Kepala Sekolah - Dora Kusumastuti, Sutoyo & (Exsplorasi, 2011)
ABSTRACT A head master is the highhest leader of educational organization, as it is written in Act No. 32 Year 2004. The Act said that the authority of a head master’s transfer or mutation is in the hand of local government. As a result, the born of this act carries political issues. Permendiknas (Act of National Education Ministry) No. 28 Year 2010, for example. There’s a change about teacher’s apponmentt to replaces the authority of mutating headmaster from government to local government. Besides that, therefore, the aim of this research is to understand Permendiknas No.28 Year 2010 is against the act No. 32 Year 2004. This research is anormative /doctrinal law research that analysis the secondary data in act no. 32 Year 2004 about local government. From this research, it can conclude that Permendiknas No. 28 year 2010 about teacher appoinment to become headmaster doesn’t take the authority from local government. It only has the authority to arrange the mechanism of a headmaster’s appoinment meanwhile, it is the authority of a government to prepare, to train and to appionment a headmaster. Keywords: permendiknas, Headmaster’s mutation, local government  Act.